'Stromatolites' built by sponges and microbes – a new type of Phanerozoic bioconstruction. (30th December 2015) - Luo, Cui; Reitner, Joachim
Abstract : Two 'stromatolites' from Carboniferous and Triassic carbonates previously regarded as microbial bioconstructions are analysed and reinterpreted as sponge‐microbial build‐ups. The automicritic aggregations in these build‐ups are similar to the previously reported fossils of keratose demosponges in showing moulded anastomosing filamentous structures. All the studied columnar or domal constructions were formed in turbulent water with high sedimentation rate. The Carboniferous build‐ups were constructed in the shallow subtidal zone of an open shelf or a ramp. The laminations within the stromatolite‐like columns are composed of alternating dark micritic laminae of sponge fossils and pale laminae of neomorphic microspars. The accretion of these columns is probably related to the repeated cycles of sponge growth, rapid lithification after burial, re‐exposure and erosion, and settlement of new generations. The Triassic rocks are presumed to have been precipitated in a slightly evaporitic environment based on lithological features. They show a transition from planar laminae, which were formed under the influence of microbial mats, to stromatolitic columnar or domal build‐ups, which are dominated by stacked micritic clumps of probable sponge fossils. The sponge–microbe alternation may have been controlled by variation of salinity. Comparable with a recent study, this work shows that sponge‐related bioconstructions can be morphologically similar to microbialites in the level of mega‐ and mesostructures.